RESEARCH ALGORITHM FOR THE DEVELOPMENT OF COMMUNICATIVE COMPETENCE OF FUTURE SPECIALISTS IN PSYCHOLOGY - Shkurko, Anhelina (Mountain School of Ukrainian Carpaty, 2022)
The article presents an algorithm for researching the development of communicative competence of future specialists in psychology. The scientific-pedagogical, psychological and special literature was analyzed in order to clarify the relevance of research in this direction. The scientific apparatus of scientific research has been defined (the object of the study is the process of professional training of future specialists in psychology; the subject of the study is the structuralfunctional model of the system for the development of communicative competence of future specialists in psychology; the aim of the study is to theoretically explain the structural-functional model of the system of development of communicative competence of future specialists in psychology and to test its effectiveness experimentally); tasks, hypothesis (the development of communicative competence of future specialists in psychology will be carried out more effectively if it is based on well-founded theoretical and methodological foundations, structural components of communicative competence of future specialists in psychology, will be evaluated according to the specified criteria and will be implemented by introducing the system of their training into the educational process) and characterized methods (theoretical: systematic and comparative analysis; modeling method; generalization of the results of the pedagogical experiment; empirical: pedagogical experiment; diagnostic methods; methods of mathematical statistics). The author of the article comes to the conclusion that the presented research algorithm for the development of communicative competence of future specialists in psychology is optimal, and the practical value of the work serves as a basis for improving the level of professional training of future specialists in psychology. The author sees the prospects for further scientific work in: a detailed study of the problems of the development of communicative competence of future specialists in psychology; the definition of the conceptual and terminological apparatus of the study; development of the criterion apparatus and theoretical substantiation and practical implementation of the structural-functional model of the system of the investigated phenomenon.